Conflict of Customary Law and Positive Law in Determining The Status of Children: Criminal Implications for Children's Rights and Legal Protection - Hadibah Zachra Wadjo; Judy marria saimima; Harly Clifford Jonas Salmon (Journal of Adat Recht, 2025)
This study discusses the normative conflict between customary law and positive law in determining the status of children in Indonesia, with an emphasis on the juridical implications for the protection of children's rights. In the context of legal pluralism recognized by Article 18B paragraph (2) of the 1945 Constitution, customary law often rejects the recognition of children out of wedlock, children of serial marriages, and adopted children who do not conform to local kinship norms. This is contrary to the principles of non-discrimination and the best interests of children as stipulated in Law No. 35 of 2014 concerning Child Protection. The inconsistency of these norms not only has an administrative impact, but also raises the potential for criminal offenses, including child neglect due to not being officially recorded. This study uses a normative juridical approach with qualitative analysis methods on primary and secondary legal materials, including international conventions such as CRC. The results of the analysis show the urgency of legal harmonization through responsive derivative regulations, legal understanding by local actors, and the transformation of customary law values to be in line with the principles of child protection. Law No. 35 of 2014 is positioned as a transformational instrument to bridge the tension between local norms and national laws to ensure that children's rights are guaranteed comprehensively without discrimination